Internalizing behavioral problems in pediatric patients with congenital heart disease - Siti Annisa Dewi Rani; Irwanto; Taufiq Hidayat (Zdorovʹe Rebenka)
Background. Congenital heart disease (CHD) is the most common congenital anomaly in newborns. Advances in medical and surgical care have improved survival rates, but children with CHD remain vulnerable to psychosocial and behavioral problems. The purpose was to evaluate the prevalence and factors associated with behavioral problems in pediatric patients with CHD. Materials and methods. A cross-sectional analytical study was conducted at Dr. Soetomo General Hospital, Surabaya, from July to October 2024. Pediatric patients aged 4–17 years with CHD were assessed using the Pediatric Symptom Checklist-17 (PSC-17). Differences in behavioral problems between acyanotic and cyanotic CHD groups were analyzed, and associated risk factors were identified through logistic regression analysis. Results. Among the 101 participants, 30 (29.7 %) had positive PSC-17 scores, with internalizing problems being the most common (22 subjects, 77.3 %). A significant difference in internalizing scores was found between acyanotic and cyanotic CHD groups (p = 0.036). No significant differences were observed in attention, externalizing, or mixed subscales. Younger age (< 10 years) in acyanotic CHD and male gender, lower parental education, and working mothers in cyanotic CHD were identified as significant risk factors for internalizing behavioral problems. Conclusions. Internalizing behavioral problems are prevalent among pediatric CHD patients, with significant differences between acyanotic and cyanotic CHD.